A collection of Sabellidae (Polychaeta) from Carrie Bow Cay (Belize, western Caribbean Sea) with the description of two new species - Giangrande, Adriana; Licciano, Margherita; Gambi, Maria Cristina (Zootaxa, 2007)
In the framework of a research on taxonomy and ecology of selected families of polychaetes conducted at the field station of the Smithsonian Institution (Washington DC, USA) at Carrie Bow Cay (Belize, Western Caribbean Sea) on November 2005, several qualitative benthic samples from different habitats and substrate types (Thalassia testudinum shoots, fragments of dead hard corals, sponges) have been analyzed. In some of these samples, specimens of Sabellidae were found, revealing, together with some taxa already known for the area, the presence of two new species, Megalomma fauchaldi sp. nov., and Pseudoaugeneriella spongicola sp. nov., this latter representing a genus newly reported from the Caribbean. Sabellidae biodiversity and systematics between Caribbean and Mediterranean regions is also compared.